Fucoidan-Based Nanoparticles for Diabetic Complications: Mechanisms, Therapeutic Opportunities, and Translational Challenges - Sri Agus Sudjarwo Agus Sudjarwo; Giftania Wardani; Rochmah Kurnijasanti; Mohd Rais Mustafa (Natural Resources for Human Health, 2026)
Diabetes mellitus is a major chronic metabolic disorder that imposes a growing global health burden, largely because of its progressive microvascular and macrovascular complications. Persistent hyperglycaemia promotes oxidative stress, chronic inflammation, endothelial dysfunction, fibrosis, and impaired tissue repair, while currently available therapies remain limited by incomplete target specificity and suboptimal tissue-level protection. Fucoidan, a sulfated polysaccharide derived from brown seaweed, has attracted increasing interest because of its antioxidant, anti-inflammatory, antifibrotic, and cytoprotective activities. However, the therapeutic performance of free fucoidan is often constrained by structural heterogeneity, variable bioavailability, and insufficient delivery to diseased tissues. This review examines the emerging role of fucoidan-based nanoparticles as a strategy to overcome these barriers and to expand the translational relevance of fucoidan for diabetic complications. The discussion integrates current evidence on mechanistic pathways, complication-specific applications, formulation advantages, and translational bottlenecks. Overall, fucoidan-based nanoparticles appear capable of simultaneously modulating several core pathogenic drivers of diabetic complications, including oxidative stress, inflammatory signalling, vascular injury, extracellular matrix remodelling, apoptosis, and defective regeneration. Their strongest near-term potential appears to be in diabetic wound healing, although applications in diabetic nephropathy, retinopathy, neuropathy, and cardiovascular injury are also conceptually promising. Despite this promise, major challenges remain in source standardisation, nanoformulation reproducibility, pharmacokinetic characterisation, safety evaluation, and regulatory readiness. Fucoidan-based nanoparticles therefore represent a compelling but still preclinical therapeutic platform, and future progress will depend on more rigorous mechanistic studies, clinically relevant models, and translation-oriented formulation design.